1996
DOI: 10.1002/anie.199601771
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Chain Polyprenyl Phosphates Form “Primitive” Membranes

Abstract: COMMUNICATIONSwhich allows structural information to be deduced from a measured vibrational spectrum. Strong hydrogen bonds with short 0-0 distances correlate with long, weakened 0 -H covalent bonds and low hydrogen stretching vibrations. If the 0-0 distance is increased. the length ofthe covalent bond approaches its unperturbed value approximately exponentially; the 0 -H stretching vibration increases almost linearly as the length of the covalent bond decreases. Aluminum-rich zeolites differ from their alumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…2E). These amphiphiles can self-assemble into vesicles (Ourisson and Nakatani 1994;Pozzi et al 1996). In an interesting parallel to fatty-acid membranes, which can be stabilized to pH changes by acyl alcohols , polyprenyl phosphate membranes are stabilized by addition of polyprenyl alcohols (Streiff et al 2007).…”
Section: Self-assembled Vesicles To Protocellsmentioning
confidence: 99%
“…2E). These amphiphiles can self-assemble into vesicles (Ourisson and Nakatani 1994;Pozzi et al 1996). In an interesting parallel to fatty-acid membranes, which can be stabilized to pH changes by acyl alcohols , polyprenyl phosphate membranes are stabilized by addition of polyprenyl alcohols (Streiff et al 2007).…”
Section: Self-assembled Vesicles To Protocellsmentioning
confidence: 99%
“…A dramatic effect of the growth temperature on the biosynthesis of haslenes was also reported (15), suggesting that these isoprenoids may have a significant biological function in diatoms. Pozzi et al suggested that phosphate esters of acyclic isoprenoids, including haslenes, may be membrane lipids (16), and Takajo and coworkers (17) showed that synthetic HBI phosphates formed stable vesicles. As yet, the location and biological function of HBIs in diatoms are not known.…”
mentioning
confidence: 99%
“…Several authors (Berti et al 1998;Bloechliger et al 1998;Luisi et al 1999;Pozzi et al 1996;Takajo et al 2001) consider that the spontaneous formation of membranes is one of the primordial steps in prebiotic evolution. One plausible model for the prebiotic formation of proto-cellular compartments, the spontaneous formation of stable vesicles, characterized by an inner and an outer space separated by a semi-permeable membrane, is a well-known and reproducible process in water.…”
Section: The Importance Of Water For the Origin Of Lifementioning
confidence: 99%